Evaluate five different diagnostic tests for dry mouth assessment in geriatric residents in long-term institutions in Taiwan - Cheng, Yao-Ming (BMC Oral Health, 2019)
BACKGROUND: Residents in long-term care (LTC) institutions require care plans to effectively resolve dry mouth. Simple and easily comprehensible dry mouth indices must be developed to assist care professionals in determining dry mouth among residents. Therefore, this study aim of the study was to evaluate five different diagnostic tests for dry mouth assessment. METHODS: A total of 568 residents were recruited from several LTC institutions in central Taiwan. The research instruments and tools comprised of the characteristics of the residents, state of oral health care, self-perceived ability to chew food, Taiwanese short-form of the Oral Health Impact Profile (OHIP-7 T), self-perceived levels of dry mouth, oral moisture checking, and a repetitive saliva swallowing test (RSST). The data collected were analyzed through demographic analysis, Correlation coefficient and chi-squared automatic interaction detection. RESULTS: Results of the decision tree analysis indicated that RSST results, tooth brushing frequency, and age were the three indices that exerted the greatest influence on oral moisture levels. Specifically, in residents with relatively high RSST results, a daily tooth brushing frequency > 1, and an age < 68 years exhibited more favorable oral moisture levels. The results indicated that residents’ self-perceived oral status was not associated with their oral moisture levels. CONCLUSION: The three indices can be provided to LTC institutions for on-site assessment of dry mouth among residents to facilitate early detection of those with dry mouth.